Dampak Cyberslacking pada Tingkat Pembelajaran Mahasiswa - Nurwahyuni Nasir; Sandra Adetya; Yomima Viena Yuliana (Journal on Education, 2023)
Internet access is now easier to get. The internet has also become one of the necessities of human life today. Many benefits and conveniences of life are created thanks to the existence of the internet. Especially in the world of education. Higher education is one level of education that cannot be separated from the need for internet access. In order to meet the material needs at the higher education level, students have a high urgency to use the internet. However, the use of the internet, which should have many benefits, in fact causes cyberslacking activities. Namely the activity of using the internet during class hours to access things that have nothing to do with learning material. This is thought to be the cause of the poor student learning rate. Therefore, the purpose of this study is to analyze the effect of cyberslacking on student learning. The method used is correlational quantitative. Namely a quantitative method that explains the relationship of an event mathematically. The data used is primary data sourced from the author's observation using a research instrument in the form of a questionnaire. The results of the study show that there is a relationship with the level of high probability that students with higher levels of cyberslacking have the potential to get lower grade point average scores. There are several factors that can explain why students carry out cyberslacking actions, both from the environment and personal